2006
DOI: 10.1007/s10661-006-9365-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Controlling Factors to Ali/(Ca + Mg) Molar Ratio in Acidic Soil Water, Southern and Southwestern China: Multivariate Approach

Abstract: Al i /(Ca + Mg) molar ratio in soil water has been used as an indicator to the effects of acid deposition on terrestrial ecosystems. However, the main factors controlling this ratio have not been well documented in southern and southwestern China. In this study, we presented the variation in inorganic aluminum (Al i ) and Al i /(Ca + Mg) molar ratio in different sites and soil horizons based on two to three years monitoring data, and evaluated the main factors controlling Al i /(Ca + Mg) molar ratio using prin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Other studies, which have taken this approach, are few and have examined concentrations of Al and Al fractions in soil samples rather than stream water samples (Borůvka et al 2005(Borůvka et al , 2007Guo et al 2007). Transect studies have shown that Al concentration and speciation undergo large changes in the lateral transport from recharge zone to discharge into the stream (Cory et al 2007b) with the riparian zone identified as especially important (Pellerin et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies, which have taken this approach, are few and have examined concentrations of Al and Al fractions in soil samples rather than stream water samples (Borůvka et al 2005(Borůvka et al , 2007Guo et al 2007). Transect studies have shown that Al concentration and speciation undergo large changes in the lateral transport from recharge zone to discharge into the stream (Cory et al 2007b) with the riparian zone identified as especially important (Pellerin et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The statistical When co-linearity relationships exist between each independent variable, errors will occur in the results of linear regression. Therefore the partial least squares regression was utilized to reduce the errors (Guo et al, 2007).…”
Section: Methods For Data Analysismentioning
confidence: 99%
“…TSP is a coniferous-broad-leaved mixed forest ecosystem, dominated by massone pine (Pinus massoniana); Chinese fir (Cunninghamia lancelota) is also common. The forest in the area has been planted since 1962, because large parts of the forests in China were logged between 1958 and 1962 during the Great Leap Forward (Guo et al 2007). Prior to this, the forest area had several plots used for rice and vegetable production.…”
Section: Site Descriptionmentioning
confidence: 99%